2013
DOI: 10.1177/1069072713498483
|View full text |Cite
|
Sign up to set email alerts
|

Strengths-Based Career Counseling

Abstract: This study implemented an innovative model of individual Strengths-Based Career Counseling (SBCC), as carried out by vocational counseling psychologists, and measured its impact on unemployed job seekers. As part of a quasi-randomized pre–post intervention study, career counseling clients completed self-esteem, career exploration, strengths use, and life satisfaction scales prior to the initial counseling session (T1) and immediately following the final session (T2). A follow-up was carried out at 3 months pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 41 publications
2
53
1
Order By: Relevance
“…The original English version of the SUS has already been translated into Hebrew (Littman-Ovadia et al, 2014) with good reliability (Cronbach α from 0.88 to 0.92) in a study focusing on strengths-based career counseling. Moreover, a work-adapted SUS version built upon the original scale is existing in English (Kong and Ho, 2015) and French (Dubreuil et al, 2014) as well as a Dutch translation (van Woerkom and Meyers, 2015), partially built upon the ‘Strengths Knowledge Scale’ and the SUS (Govindji and Linley, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The original English version of the SUS has already been translated into Hebrew (Littman-Ovadia et al, 2014) with good reliability (Cronbach α from 0.88 to 0.92) in a study focusing on strengths-based career counseling. Moreover, a work-adapted SUS version built upon the original scale is existing in English (Kong and Ho, 2015) and French (Dubreuil et al, 2014) as well as a Dutch translation (van Woerkom and Meyers, 2015), partially built upon the ‘Strengths Knowledge Scale’ and the SUS (Govindji and Linley, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The mere act of filling out this type of survey and being aware of one’s strengths can be a helpful intervention [12-14]. However, researchers have suggested that providing some type of support and guidance on how to better use one’s personal strengths through coaching [15], development programs [11], or counseling [16], for example, is even more beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to facilitating growth include expanding support networks (e.g., strengthening therapeutic relationships, offering clinical groups), exploring meaning in the client's life, and focusing on client strengths and resilience. When practicing from a strengths-based approach, counselors might find it useful to (a) identify client strengths, (b) celebrate client accomplishments, and (c) identify the meaning and benefit behind strengths (Littman-Ovadia, Lazar-Butbul, & Benjamin, 2014). The current study suggests that trauma symptoms could add to clients' resiliency and adaptability, whereby clients find additional strengths or potential meaning from their trauma experiences.…”
Section: Implications For Counselingmentioning
confidence: 85%